2011
DOI: 10.1007/s00393-011-0852-0
|View full text |Cite
|
Sign up to set email alerts
|

„Treat-To-Target“ aus der Sicht der niedergelassenen Rheumatologie

Abstract: The development of evidence-based treat-to-target (T2T) recommendations alleviates decision-making for the rheumatologist and simultaneously promises substantial improvement of outcome for rheumatoid arthritis (RA) patients. For the office-based rheumatologist in Germany, however, implementation of T2T recommendations contains several difficulties. Limitations arise as a result of an insufficient number of rheumatologists as well as a lack of adequate remuneration both resulting in a lack of time for the indiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 15 publications
1
6
0
Order By: Relevance
“…Comparing the number of RA patients in Austria and their general practitioner (GP) counterparts makes it evident that an Austrian primary care physician is confronted with 0.4 incident patients with RA per year (that is, dividing the number of office-based GPs by the number of incident RA patients in Austria). This number is in line with published German studies [7, 8]. It is well established that diagnostic accuracy is a function of frequency - and for diseases as infrequent as RA a variety of approaches exist that try to stimulate more rapid and integrated cooperation between GPs and specialists [911].…”
Section: Introductionsupporting
confidence: 80%
“…Comparing the number of RA patients in Austria and their general practitioner (GP) counterparts makes it evident that an Austrian primary care physician is confronted with 0.4 incident patients with RA per year (that is, dividing the number of office-based GPs by the number of incident RA patients in Austria). This number is in line with published German studies [7, 8]. It is well established that diagnostic accuracy is a function of frequency - and for diseases as infrequent as RA a variety of approaches exist that try to stimulate more rapid and integrated cooperation between GPs and specialists [911].…”
Section: Introductionsupporting
confidence: 80%
“…The implementation of guidelines in rheumatology clinical practice has been shown to be a challenge. Studies in rheumatoid arthritis indicate that there is a discrepancy between the reported acceptance of guidelines and the application of these in clinical practice [ 16 , 17 ]. The IRIS study even showed that despite participation in 2 years of educational training, rheumatologists seem to be reluctant to apply recommendations in real-life clinical practice [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…This could be improved by increasing the number of physicians, introducing structured patient information and increasing involvement of assistants and nurses. 30 With the development of therapeutic options like biologic agents rheumatologists acknowledge the need to involve the patients in the treatment decisions, as this has been shown to improve their adherence to therapy. 31 Another driver to implement the concept of shared decision making could be the fact that patient participation is increasingly seen as a quality indicator for medical care within the German health care system.…”
Section: Discussionmentioning
confidence: 99%